Biotransformation of tobacco-derived Z-abienol into precursors of ambrox by newly identified Acinetobacter tjernbergiae LSC-2 - Xi, Gaolei; Qi, Wenyuan; Rasool, Aamir; Zhao, Yongzhen; Wang, Qingfu; Zhang, Liuke; Chen, Haoyang; Zhang, Xinlong; Huang, Shen; Chen, Zhifi (Frontiers in Microbiology, 2025)
Z-abienol is a labdane diterpene present in tobacco leaves and is a key precursor for producing valuable aroma compounds such as ambrox. This study aimed to identify and characterize a bacterial strain that can efficiently degrade Z-abienol through microbial fermentation. The strain LSC-2 isolated from fresh tobacco leaves was identified as Acinetobacter tjernbergiae based on its morphological features and 16S rDNA phylogenetic analysis. Results of fermentation optimization experiments showed that the highest degradation efficiency of LSC-2 (69.3%) was achieved under the following conditions: 1 mg/mL Z-abienol, 0.5 mg/mL urea as the nitrogen source, pH 7, 30°C, and 150 rpm over 4 days. Whole-genome sequencing and functional annotation revealed that oxidoreductases, especially those from the auxiliary activity enzyme family, play a critical role in Z-abienol degradation. High-performance liquid chromatography and gas chromatography–mass spectrometry analysis confirmed the biotransformation of Z-abienol into various intermediates, including sclareol (211.3 μg/mL), scalaral (89.5 μg/mL), and amberonne (57.0 μg/mL). These intermediates have significant industrial applications, particularly in fragrance, pharmaceutical, and cosmetic industries. Sclareol serves as a key precursor in ambrox synthesis, a widely used fixative in high-end perfumery, whereas scalaral and amberonne enhance the aroma in tobacco and flavor formulations. The findings of this study provide valuable insights into the microbial degradation of Z-abienol, which will help develop a sustainable approach to producing bio-based fragrance compounds. Future studies should focus on enzymatic mechanisms and metabolic engineering strategies to improve the efficiency of biotransformation.